(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article talks about educating elementary school students in the national spirit through folk art. Studying the essence of genres of folk art in primary school reading textbooks. Studying genres such as fairy tales, proverbs, riddles, parables given in the primary school textbook in harmony with our national values. Moral education of students, inculcation of human qualities, and formation of thinking through folk art.